Public Administration, Democracy and Peacebuilding in the Democratic Republic of the Congo - Jean Chrysostome K. Kiyala; Mulanda J. Juma; Dorcas Ettang (AOSIS, 2025)
The Democratic Republic of Congo (DRC) presents a striking paradox: vast natural and mineral wealth coexist with persistent poverty, weak infrastructure and fragile institutions. Kiyala's four-part scholarly book explores these tensions, aiming to identify practical and effective strategies to address the country's complex challenges. To meaningfully confront the DRC's enduring crises, Kiyala argues that public administration must engage with key drivers of insecurity and instability. These include: - Employing the Dodd–Frank Act's Section 1502 on conflict minerals, particularly the impact of the de facto embargo on the 3Ts (tin, tungsten and tantalum) - The question of Congolese citizenship for the Banyamulenge (Tutsi communities of the DRC) and the need for legislative clarity - Regional and international collaboration to address ongoing threats to peace, such as the remnants of the FDLR and other armed groups - The complex integration of the M23 movement and other armed factions into the national army through effective screening, vetting and identification processes - The revitalisation of transitional justice, reconciliation and national healing efforts. Without addressing these core issues with resolve and coherent strategies, efforts toward lasting peace and sustainable development will remain elusive. The book also introduces the peacebuilding evolution systems theory (PBEST), a novel framework that integrates peacebuilding theory with insights from neuroscience. The PBEST emphasises the progressive development of peace, from individual disposition to collective, global action for domestic and international security. Rich in empirical analysis, this scholarly work offers significant insights not only for scholars and researchers but also for practitioners and policymakers in African studies, political science, public administration and conflict resolution.